2018
DOI: 10.1556/2006.7.2018.128
|View full text |Cite
|
Sign up to set email alerts
|

Young people’s recall and perceptions of gambling advertising and intentions to gamble on sport

Abstract: BackgroundThere has been an increased international policy focus on the factors that may contribute to, and prevent, the normalization of gambling for young people. However, there is still limited research, which investigates the role of advertising in shaping young people’s gambling attitudes and consumption intentions.MethodsMixed methods study of 111 young people aged 11–16 years recruited from community basketball stadiums in Victoria, Australia, between May and July 2018. Interviewer-assisted surveys inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 36 publications
1
29
0
1
Order By: Relevance
“…These factors should be considered as potentially important contextual drivers of harm. This is further reflected in the rapidly changing environment in terms of advertising exposure and its impact that is being highlighted within the international literature, specifically on young people (14) and gambling populations more generally [for example, (15,16)].…”
Section: Introductionmentioning
confidence: 99%
“…These factors should be considered as potentially important contextual drivers of harm. This is further reflected in the rapidly changing environment in terms of advertising exposure and its impact that is being highlighted within the international literature, specifically on young people (14) and gambling populations more generally [for example, (15,16)].…”
Section: Introductionmentioning
confidence: 99%
“…They do not reflect the current gambling landscape in which a range of products, industry promotional strategies and gambling environments may increasingly expose, appeal to or target women with a range of different gambling opportunities. For example, recent research found that regardless of gender, young people who were engaged in sport had high-level recall of gambling advertising and positive attitudes towards gambling products [32]. This indicates that young women may be equally at risk of gambling harm as young men, when exposed to industry advertising [32].…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent research found that regardless of gender, young people who were engaged in sport had high-level recall of gambling advertising and positive attitudes towards gambling products [32]. This indicates that young women may be equally at risk of gambling harm as young men, when exposed to industry advertising [32].…”
Section: Introductionmentioning
confidence: 99%
“…One striking feature of this new offer of online gambling is the advent of in-play betting that allows sports bettors to place bets during the game (e.g., on the final outcome of the game, on key events within the game, or on a particular discrete event during a game; [67]). As such, a countless number of sport events continuously promote gambling opportunity, a phenomenon that has already been linked to an increased willingness to bet in sport fans (including children; [•8,6871]). Moreover, in contrast to other types of gambling activities, sports betting is not negatively connoted in our society (e.g., [72]).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, recent research findings have highlighted that despite having never gambled, some young sports fans displayed technical knowledge of sports betting, including being able to discuss and describe “odds”, different gambling markets, and how to place bets [69]. This betting-related knowledge could be predominantly traced back to the abiding marketing they were faced with (e.g., pop-up messages occurring during live sports events that feature dynamic betting ratios; [80]), inducing increased recall and awareness of sports betting brands, or perceptions of promotional strategies [68,69,81,82]. As such, this ubiquity of cues might increase the incentive salience of sports betting in young individuals long before they reach the minimum legal age for gambling.…”
Section: Introductionmentioning
confidence: 99%